Case of caval lobular capillary hemangioma mimicking tumor thrombus. Issue 2 (16th January 2019) - Hashimoto, Sho; Obinata, Daisuke; Yamaguchi, Kenya; Sakurai, Fuminori; Yoshida, Toshiyuki; Yoshizawa, Tsuyoshi; Matsui, Tsuyoshi; Mochida, Junichi; Masuda, Shinobu; Takahashi, Satoru
Abstract : Introduction: We presented a rare case of caval lobular capillary hemangioma. Case presentation: A 66‐year‐old female visited our department complaint with shadow defect in vena cava of right renal hilum appeared on computed tomography for periodically checking 3 years after radical hysterectomy with bilateral ovariectomy. Abdominal computed tomography identified a shadow defect of 35 mm in diameter in the inferior vena cava continuing posteriorly to a 35 mm mass of retroperitoneum. During the total removal of this lesion, we identified the lesion was connected to right ovarian vein. The specimen consisted of microcapillaries which formed reticular structure. Immunostaining of specimens identified positive CD31, CD34, and Factor 8 in all cells. Ki67 antibody was positive at 2–3% of all cells. These findings suggested the tumor was intravenous lobular papillary hemangioma. Conclusion: This is the first report of intravenous lobular papillary hemangioma originated from right ovarian vein and extended to inferior vena cava.